Basic Principal for Reading of Chest X Ray Acording to International Labour Organization (ILO) Classification for Pneumoconiosis - Agus Dwi Susanto (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2019)
Pneumoconiosis is disease that caused by deposition of dust in lung parenchymal with fibrosis was result of it’s reaction. Usually pneumoconiosis diagnose and classified by conventional chest x ray. The International Labour Organization (ILO) described standard system for classified radiograph abnormality of pneumoconiosis based on parenchymal and pleural abnormality. Parenchymal abnormality divided into 2 categories that is small opacities and large opacities. Description steps of chest X ray reading based on ILO classification was technical quality, parenchymal abnormality (shape and size, affected zone and profusion), pleural abnormality (localized, width, extent and severity of calcification) and other abnormality with recorded by symbols (J Respir Indo. 2019; 39: 272-9)